Measuring and managing credit risk - Servigny, Arnaud de.; Renault, Olivier (New York : McGraw-Hill, 2004)
Takes you far beyond the Basel guidelines to detail a powerful, proven program for understanding and controlling your firm's credit risk. Providing hands-on answers on practical topics from capital management to correlations, and supporting its theories with up-to-the-minute data and insights, this authoritative book examines every key aspect of credit risk.
Includes bibliographical references.
oif 27/08/15
Loan
Keywords: Credit -- Management -- Mathematical models; Risk management -- Mathematical models; Credit ratings; Derivative securities; Default (Finance)